Performance of Disk Mill Type Mechanical Grinder for Size Reducing Process of Robusta Roasted Beans - Sri Mulato; Sukrisno widyotomo; Hadi Karia Purwadaria (Indonesian Coffee and Cocoa Research Institute, 2007)
One of improtant steps in secondary coffee processing that influence on final product quality such as consistency and uniformity is milling process. Usually, Indonesian smallholder used